Thermal comfort and user’s perception of bamboo as shelter in school outdoor environment - Bigdeli, Mani Mansouri (2017)
The quality of outdoor and semi-outdoor spaces influences the well-being and performance of people. Among many factors, thermal conditions play a significant role in the satisfaction of individuals in such areas. The exploration of human thermal comfort in outdoor and semi-outdoor spaces, especially in a tropical climatic condition, is vital, and the numbers of studies which mainly focus on this context are few. A bamboo shelter, as a semi-outdoor space, can significantly affect the thermal comfort of users during the day. Hence, the primary purpose of this study is to focus on the general user’s perception of the semi-outdoor shelters located at Secondary School (S.S) and Primary School (P.S) in Serdang, Malaysia. Consequently, a quantitative field study together with a subjective questionnaire survey were conducted to evaluate thermal sensation and thermal preferences of respondents, simultaneously. The results of the quantitative field study and questionnaire survey revealed that the bamboo shelter located at the P.S provides a better thermal state and are more comfortable to the respondents in their thermal condition. Moreover, the results of this study also illustrates that shading has a significant effect on the thermal satisfaction of people and well-covered spaces provide a better thermal environment for users. The findings of this study can be applied in future design decision-making, concerning outdoor and semi-outdoor spaces to provide thermally comfortable non-indoor spaces that can lead to increasing the usage of such spaces. In conclusion, the findings of this study contribute towards improving the design of shelters as semi-outdoor spaces for users in the tropical climate of Malaysia to enhance the quality of life in urban areas.